BAURAN PEMASARAN PRODUK OLAHAN MAKANAN RINGAN PRODUKSI AROMA JAYA DESA SUMBER REJO KECAMATAN MODAYAG KABUPATEN BOLAANG MONGONDOW TIMUR (Marketing Mix of Processed Snack Food Produced by Aroma Jaya Sumber Rejo Village, Modayag Sub District, East Bolaang Mongondow Regency) - Anjas Ambarak; Lyndon R. J. Pangemanan; Ellen G. Tangkere (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
The objective of this research is to describe the marketing mix of processed snack products produced by "Aroma Jaya" Sumber Rejo Village, Modayag Sub District, East Bolaang Mongondow Regency. This research was carried out for 1 month starting April 2021. The data used in this study were primary and secondary, primary data will be taken by survey by giving direct questions to consumers, using questionnaires as a data collection tool containing questions that related to this research and secondary data obtained from these businesses related to this research, such as the history of Aroma Jaya business. The data analysis used in this study is a descriptive analysis analyzed by usingÂ  Likert scale. Based on the results and discussions that have been carried out, it can be concluded that the consumer's assessment of the Aroma Jaya company's marketing mix actions using the 4P related to the four variables, namely product, price, place and promotion shows a very good category.Â